(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article summarizes the taxing thoughts on jewelry and their semantics, which at the end of the XIX and beginning of the XX centuries occupied a special place in the everyday life of Uzbek women of the Fergana Valley. In the lexical-semantic variants of the jewelry of the women of the Fergana Valley, the distinctive and, alternatively, common features of various objects and objects were expressed, and it was also believed that the local population embodied the unique magik or healing properties of each item.